1999
DOI: 10.1016/s0895-7061(99)00220-4
|View full text |Cite
|
Sign up to set email alerts
|

β-blockers and diuretics: to use or not to use

Abstract: The present review scrutinizes the recommendations of many guidelines to use beta-blockers and diuretics as first-line therapy in hypertension. These recommendations were ostensibly based on multiple prospective randomized trials attesting to a reduction of morbidity and mortality with both beta-blockers and diuretics in monotherapy as well as in combination. Although diuretic-based therapy has been shown to prevent strokes (and, to a lesser extent, heart attacks, and cardiovascular and all-cause mortality), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Although β-blockers did have a beneficial effect on the BP, β-blocker therapy failed to favourably affect the cardiovascular events and mortality either alone or in combination with a diuretic [22]. Warmack reviewed and evaluated 5 placebo- controlled studies, 10 active-controlled studies and 11 meta-analyses for assessing the effects of β-blockers on cardiovascular and cerebrovascular outcomes in the treatment of hypertension.…”
Section: Reviewmentioning
confidence: 99%
“…Although β-blockers did have a beneficial effect on the BP, β-blocker therapy failed to favourably affect the cardiovascular events and mortality either alone or in combination with a diuretic [22]. Warmack reviewed and evaluated 5 placebo- controlled studies, 10 active-controlled studies and 11 meta-analyses for assessing the effects of β-blockers on cardiovascular and cerebrovascular outcomes in the treatment of hypertension.…”
Section: Reviewmentioning
confidence: 99%
“…The use of β blockers has achieved success in hypertension, particularly in patients with associated coronary artery disease. A meta‐analysis to evaluate the effects of treatment with β blockers in the elderly suggested that thiazides are superior to β blockers in this population in the control of blood pressure and reduction of the cardiovascular event rate 43 . However, this meta‐analysis has been questioned because the majority of patients received both diuretics and β blockers, and much of the difference between agents occurred in a single trial with a high drop‐out rate 44 .…”
Section: Sympathetic Nervous System Attenuationmentioning
confidence: 99%
“…A meta-analysis to evaluate the effects of treatment with β blockers in the elderly suggested that thiazides are superior to β blockers in this population in the control of blood pressure and reduction of the cardiovascular event rate. 43 However, this meta-analysis has been questioned because the majority of patients received both diuretics and β blockers, and much of the difference between agents occurred in a single trial with a high drop-out rate. 44 Although β blockers are still advocated by some as a suitable first-line therapy for elderly patients, 45 some experts would not use β blockers as monotherapy for the elderly hypertensive patient despite the fact that their use reduces strokes and congestive heart failure in this population.…”
Section: Sympathetic Nervous System Attenuation Beta Blockersmentioning
confidence: 99%
“…For several years, the beneficial effects of β blockers for hypertension have come under intense scrutiny by a number of investigators. Messerli et al 16,17 examined 10 trials involving 16,164 elderly patients randomized to diuretics and/or β blockers. Diuretic therapy was found to be superior to β blockers in this patient population for controlling blood pressure and reducing cardiovascular events.…”
Section: Redefining the Role Of β Blockers As First‐line Therapymentioning
confidence: 99%